2020
DOI: 10.1042/bsr20201276
|View full text |Cite|
|
Sign up to set email alerts
|

miR-135a inhibits malignant proliferation and diffusion of non-small cell lung cancer cells by down-regulating ROCK1 protein

Abstract: Objective: To seek the clinical significance and regulatory mechanism of miR-135a and Rho-associated protein kinase 1 (ROCK1) in non-small cell lung cancer (NSCLC). Methods: NSCLC cells were purchased, and miR-135a-mimics, miR-135a-inhibitor, miR-NC, si-ROCK1 and Sh-ROCK1 were transfected into NSCLC cells HCC827 and NCI-H524. qRT-PCR and Western blot were used to detect the expression of miR-135a, ROCK1, Bax, Caspase3, Bcl-2, N-cadherin, vimentin and E-cadherin. MTT, scratch test, Transwell and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…In this study, miR‐135a‐5p was demonstrated to be downregulated in NSCLC tissues and cells, which was consistent with a previous study 18 . Low expression of miR‐135a was associated with poor prognosis of NSCLC patients, and miR‐135a had the potential to be a serum indicator for diagnosing NSCLC 19 . MiR‐135a‐5p could be sponged by circLARP4 in NSCLC 20 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, miR‐135a‐5p was demonstrated to be downregulated in NSCLC tissues and cells, which was consistent with a previous study 18 . Low expression of miR‐135a was associated with poor prognosis of NSCLC patients, and miR‐135a had the potential to be a serum indicator for diagnosing NSCLC 19 . MiR‐135a‐5p could be sponged by circLARP4 in NSCLC 20 .…”
Section: Discussionsupporting
confidence: 91%
“…18 Low expression of miR-135a was associated with poor prognosis of NSCLC patients, and miR-135a had the potential to be a serum indicator for diagnosing NSCLC. 19 MiR-135a-5p could be sponged by circLARP4 in NSCLC. 20 Moreover, we found that ARL5B was a target gene of miR-135a-5p, and was negatively regulated by miR-135a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…A number of ROCK1-interacting miRNAs have been found to reduce tumor burden. For instance, experiments in non-small cell lung carcinoma cells showed that the tumor suppressor roles of miR-135a ( Zhao et al, 2020 ), miR-148b ( Luo and Liang, 2018 ) and miR-335-5p ( Du et al, 2019 ) are exerted through modulation of expression of ROCK1. The interactions between miRNAs and ROCK1 have been mostly assessed in osteosarcoma cells among other cancers.…”
Section: Introductionmentioning
confidence: 99%